2022
DOI: 10.1007/s40268-022-00385-4
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Phase I Study of the Novel Injectable Calcimimetic Agent Upacicalcet in Healthy Adult Japanese Participants

Abstract: Background and Objective Upacicalcet sodium hydrate is a novel small-molecule calcimimetic and has potential as a therapeutic agent for secondary hyperparathyroidism. We assessed the pharmacokinetics, pharmacodynamics, safety, and tolerability of a single intravenous dose of upacicalcet in Japanese healthy adults. Method This was a single-center, double-blinded, randomized, placebo-controlled, dose-escalation study. For each cohort, eight subjects were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The phase I trials of calcimimetics, carried out in healthy subjects, were intended to assess pharmacokinetics, pharmacodynamics, safety, tolerability, and the efficacy of oral and intravenous molecules on the levels of PTH and other factors involved in the phosphate and calcium metabolism. However, no effects in bone were reported in these preliminary studies 50–54 . With regard to vitamin D, and also in the context of primary hyperparathyroidism without CKD, it has been documented a decreased bone turnover due to vitamin D‐mediated inhibition of PTH secretion 55,56 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The phase I trials of calcimimetics, carried out in healthy subjects, were intended to assess pharmacokinetics, pharmacodynamics, safety, tolerability, and the efficacy of oral and intravenous molecules on the levels of PTH and other factors involved in the phosphate and calcium metabolism. However, no effects in bone were reported in these preliminary studies 50–54 . With regard to vitamin D, and also in the context of primary hyperparathyroidism without CKD, it has been documented a decreased bone turnover due to vitamin D‐mediated inhibition of PTH secretion 55,56 .…”
Section: Discussionmentioning
confidence: 87%
“…However, no effects in bone were reported in these preliminary studies. [50][51][52][53][54] With regard to vitamin D, and also in the context of primary hyperparathyroidism without CKD, it has been documented a decreased bone turnover due to vitamin D-mediated inhibition of PTH secretion. 55,56 The administration of vitamin D has been also reported in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 1 and 2 clinical trials showed that its interdialytic plasma half-life was 65–122 hours in HD patients, which is markedly longer than that in healthy participants. 19,20 Moreover, its removal rate in a HD session was 79%–100%. Therefore, the plasma concentration of upacicalcet plateaus after 1 week of administration after each dialysis session, contrary to etelcalcetide.…”
Section: Introductionmentioning
confidence: 99%